2015
DOI: 10.1017/s0008423915000499
|View full text |Cite
|
Sign up to set email alerts
|

Framing Immigration in the Canadian and British News Media

Abstract: Despite an extensive dialogue on the subject of immigration, there has been little systematic cross-national investigation into the framing of immigration in the news media. Understanding the evolution of frames is an important piece of how we conceive of the link between the public's political priorities and policy makers’ responses. While the multi-directional relationships that exist between media, public policy and public opinion often pose challenges to precisely extracting media effects, there is still m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
2
35
0
6
Order By: Relevance
“…Media studies, examining the role of news messages as major socialization agent in society, typically found that immigration news is skewed to the negative (Boomgaarden & Vliegenthart, 2009;Schemer, 2014;Schlueter & Davidov, 2013;Van Klingeren et al, 2015) with multiple references to social problems and threats (van der Linden & Jacobs, 2016). There is some prior evidence that immigration has been covered from a safety and economic threat perspective in the news (Caviedes, 2015;Greussing & Boomgaarden, 2017;Lawlor, 2015). First, immigration is depicted as posing threats in terms of rising crime levels and facilitating terrorist attacks.…”
Section: Theoretical Framework Group Conflict Theory and Trends In Immentioning
confidence: 99%
“…Media studies, examining the role of news messages as major socialization agent in society, typically found that immigration news is skewed to the negative (Boomgaarden & Vliegenthart, 2009;Schemer, 2014;Schlueter & Davidov, 2013;Van Klingeren et al, 2015) with multiple references to social problems and threats (van der Linden & Jacobs, 2016). There is some prior evidence that immigration has been covered from a safety and economic threat perspective in the news (Caviedes, 2015;Greussing & Boomgaarden, 2017;Lawlor, 2015). First, immigration is depicted as posing threats in terms of rising crime levels and facilitating terrorist attacks.…”
Section: Theoretical Framework Group Conflict Theory and Trends In Immentioning
confidence: 99%
“…En la primera fase, para elaborar la lista de frame terms que utilizan los candidatos, extraemos la lista de palabras utilizadas en el debate por cada candidato, descartando las palabras gramaticales y los términos que no están relacionados sustantivamente con el contexto (Lawlor, 2015;Miller,1997;Ansager;Riechert, 1998). En el caso de que encontremos palabras que posean más de un significado, se pueden desambiguar inspeccionando el contexto de la frase donde aparecen y añadiéndoles etiquetas para que el programa compute por separado cada una de sus acepciones.…”
Section: Metodologíaunclassified
“…A continuación, realizamos un análisis de correspondencias múltiple, siguiendo el procedimiento metodológico para la extracción de encuadres utilizado en investigaciones previas (Lawlor, 2015;Luther;Miller, 2005;Miller, 1997;Andsager;Riechert, 1998;Riechert, 2001). Este análisis permite construir una matriz tridimensional con los va-lores de los eigenvectores de las palabras utilizadas durante el debate, para establecer los frame terms que aparecen en el repertorio de un solo candidato y lo diferencian del discurso del resto.…”
Section: Metodologíaunclassified
“…Así, después de los ataques terroristas del 11 de septiembre de 2001 a los Estados Unidos, los medios de comunicación estadounidenses y británicos estuvieron más propensos a conectar los inmigrantes con el terrorismo y apoyar las voces que pedían el refuerzo de los controles fronterizos (Niles, 2010). La disparidad del tono utilizado en la cobertura mediática sobre migración y migrantes también está conectada a las circunstancias OTRAS INVESTIGACIONES / R. Carniel, E. Ortega, T. Velázquez / El tratamiento de la información sobre flujos [...] y necesidades económicas, destacando, por un lado, los gastos que supuestamente los inmigrantes generan al sistema de bienestar y, por otro lado, el valor de la inmigración para el mercado laboral (Lawlor, 2015).…”
Section: Introducción Y Antecedentesunclassified